Peran Influencer, Viral Marketing, Dan Harga Terhadap Keputusan Pembelian Produk Skincare Serum Peeling Elformula - Abdat, Nafi’ah Said; Rachma, N.; Rahman, Fahrurrozi (E-JRM : Elektronik Jurnal Riset Manajemen, 2025)
Abstract This research aims to determine the role of influencers, viral marketing, and price in purchasing decisions for eformula peeling serum skincare products. The method used in this research is quantitative with a descriptive approach. Data was collected by distributing questionnaires to respondents who had used Elformula products. Data analysis was carried out using validity, reliability tests and multiple linear regression analysis. The sample was taken through non-probability sampling with a purposive sampling method with a total of 95 respondents who were students at the Faculty of Economics and Business at the Islamic University of Malang, class management major of 2021. and had previously purchased elformula products. The results of the study showed that influencers, viral marketing, and price simultaneously influenced the decision to purchase elformula peeling serum skincare products. This research is expected to provide insight for companies in designing effective marketing strategies to increase sales of Elformula peeling serum skincare products. Keywords : Influencers, Viral Marketing, Price, Purchasing Decision, Skincare Peeling Serum Formula.